Yield potential and resistance of corn (Zea mays L.) S5 generation - SITI HAFSAH; BAKHTIAR BAKHTIAR; NUR ROSLINI; FIRDAUS FIRDAUS (Jurnal Natural, 2021)
. Maize S5 generation was obtained and assembled through open pollination, from its parents possessing high yield potential and resistant to downy mildew disease, where the parents were obtained through mass selection.  The objective of this research was to evaluate the yield potential and resistance of maize S5 generation against downy mildew disease.  The research was conducted at Syngenta Seed Indonesia, Kediri Field Station, Kedungmalang Village, Papat District, Kediri Regency, East Java, from May to October 2019.  The research was employed Randomized Block Design (RBD) non Factorial with the only factor observed, 24 genotypes of maize, 5 genotypes for disease resistance assay and 4 genotypes for yield potential assay with 2 replications.  The results showed that there were 5 resistant genotypes, 18ID010125, 18ID010141, 18ID010158, 18ID010134, 18ID010118 and 18ID010122 and 7 potential genotypes to have high yield, 18ID010144, 18ID010123, 18ID006020, 18ID010135, 18ID010125, 18ID007419 and 18ID010148. The results also exhibited 3 genotypes with the highest yield and possessed high resistance against downy mildew (18ID010125, 18ID010123 and 18ID010148).